Pengaruh Media Sosial dalam Membentuk Opini Publik terhadap Konﬂik Internasional: Analisis Konﬂik Rusia-Ukraina 2022 - Kirana Andini Maheswari (Terekam Jejak Publisher, 2023)
International conﬂicts are currently worrying information and receive special attention from all citizens of the world, one of which is the Ukraine and Russia Conﬂict. In this case, the public ﬁnds out information about the conﬂict through social media and provides sympathy for the conﬂicting countries, but then it is misused by various parties. Social media has an important role in global issues, one of which is the conﬂict between countries. Social media users in getting information on the Russian-Ukrainian conﬂict are presented with not only true news but also hoaxes or fake news. In conﬂict situations, false narratives are spread on social media by irresponsible parties that can inﬂuence public opinion and complicate understanding of the actual facts. This paper identiﬁes the inﬂuence of social media in shaping public opinion towards an international conﬂict between Russia and Ukraine. Social media, which is very open, can indirectly become a forum for public discussion and convey the opinions of various points of view of social media users around the world in viewing the conﬂict. This can form diverse public opinions. This research uses a qualitative descriptive method, namely by conducting surveys through questionnaires and describing related phenomena. The delivery and receipt of information on social media must pay attention to its truth and be critical of the information obtained, and look for accurate sources of information to prevent receiving hoaxes. People who easily believe in opinions on social media, will easily be consumed by fake news, which will later lead to public opinion that does not match the facts. This means that social media users are required to think critically in receiving and dealing with opinions and responses on social media.